Pengukuran Pembelajaran E-Learning dengan Pendekatan Technology Acceptance Model - Sulistiyani Sulistiyani; Aditya Pratama (Journal on Education, 2023)
The purpose of discussing this research is to find out the measurement of learning using e-learning using the Technology Acceptance Model approach. This research is a quantitative research with a survey approach, with a population of 67 students at Pamulang University. The data analysis technique that the writer did was quantitative descriptive analysis. The analytical method uses SEMPLS with the help of SmartPLS. The results of this study concluded that the presence of PEoU has an influence on BI, PU, which means that the ease of using LMS or E-learning at Pamulang University is able to provide benefits in improving the quality of the learning process which also has an impact on students' desire to use LMS again. But inversely related to the benefits provided (PU) does not affect BI and student satisfaction in the learning process. This can happen because in the use of LMS activities are monotonous, it is necessary to have variations in learning activities using LMS.